DESCRIPTION OF ANXIETY LEVELS AMONG THE FIRST SEMESTER STUDENTS OF FACULTY OF MEDICINE UDAYANA UNIVERSITY IN FACING OBJECTIVE STRUCTURED CLINICAL EXAMINATION - Harisutha, Made Dwiki Pradnyana; Diarthini, Ni Luh Putu Eka; Laksemi, Dewa Ayu Agus Sri; Wardani, Ni Putu (E-Jurnal Medika Udayana; Vol 11 No 3 (2022): E-Jurnal Medika Udayana, 2022)
Anxiety experienced by medical students when compared to the general population of the same age has a greater prevalence and is at a higher level. Anxiety can be one of some factors that can affect exam performances which can be a determining factor in medical students’ academic achievement. One of the conditions that can cause medical students to experience anxiety in the educational process is the result of stress in facing the Objective Structured Clinical Examination (OSCE). The OSCE results can be affected by students’ exam performances. This study aims to describe the anxiety levels in first semester students of the Udayana University Faculty of Medicine in facing OSCE. This study applied cross-sectional descriptive method using primary data of anxiety levels on first semester medical students who will face OSCE for the first time dan secondary data of students’ OSCE results. Zung Self-Rating Anxiety Scale (ZSAS) questionnaire were used to collect the primary data which were retrieved only once for each student. During the study, 106 respondents data were collected, consisting of 17 to 21 years range of age, and most of them were females (61.32%). This study was resulting in the form of a description of the level of anxiety towards OSCE with the most occur anxiety level towards OSCE in medical students is mild anxiety level (84.91%), followed by moderate anxiety level (14,15%), and severe anxiety level (0,94%). The results can be used to present a basic data to conduct further research in Udayana University Faculty of Medicine as a contribution for improving student readiness in facing OSCE. Keywords: anxiety levels, objective structured clinical examination, medical students.